An Unusual Case of a Scrotal Porocarcinoma and Review of the Literature. (2nd January 2023) - Hartsough, Emily Mae; Moran, Jakob; Devins, Kyle; Wszolek, Matthew; Cornejo, Kristine M.
Abstract: Porocarcinomas are rare tumors derived from the acrosyringium and eccrine ducts, which most commonly occur on the lower extremities or head and neck region in older adults. Microscopically, they invariably demonstrate continuity with the epithelium, showing downgrowth of broad anastomosing bands with more infiltrative intradermal cords and nests of pleomorphic tumor cells with ductal lumina; an associated poroma may also be seen. We report an unusual case of a porocarcinoma arising on the scrotum of a 55-year-old man. Because of the extraordinary location and the presence of keratinizing squamous differentiation, distinction from a squamous cell carcinoma was particularly challenging. Close examination revealed the presence of a co-existing poroma, and immunohistochemistry revealed loss of YAP1 with diffuse nuclear expression of NUT in both the porocarcinoma and poroma components. This finding is particularly suggestive of a YAP1::NUTM1 fusion which has been reported to be highly specific for poroid neoplasms. Distinction of porocarcinoma from its mimics is important due to the frequent aggressive behavior of this neoplasm.